2021
DOI: 10.1186/s42077-021-00181-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between ultrasound-guided and anatomical landmark-guided block of internal branch of the superior laryngeal nerve for awake fiber-optic intubation in suspected difficult intubation: a randomized controlled study

Abstract: Background Airway anesthesia is pivotal for successful awake intubation provided either topically or by nerve blocks. The widespread use of ultrasonography allows anesthesiologists to evaluate complex and varied anatomy before needle insertion. This study aims to evaluate the effect of ultrasound-guided technique for the block of the internal branch of the superior laryngeal nerve in difficult airway patients in comparison to blind anatomical technique. Sixty patients aged 18–60 years, of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Additionally, two studies assessed the effect of ultrasound guidance compared with landmark-based techniques of the superior laryngeal nerve block [11,12 ▪▪ ]. Both studies revealed the benefit of ultrasound guidance in achieving higher quality airway anesthesia, shorter time to intubation, and increased patient comfort [11,12 ▪▪ ]. Though not described specifically in these studies, we posit that the use of ultrasound guidance for the superior laryngeal nerve block may be particularly beneficial in patients for whom landmark techniques may be more difficult, due to body habitus, aberrant anatomy, and/or distortion of normal airway landmarks.…”
Section: Regional Anesthesia Vs Topicalizationmentioning
confidence: 97%
See 4 more Smart Citations
“…Additionally, two studies assessed the effect of ultrasound guidance compared with landmark-based techniques of the superior laryngeal nerve block [11,12 ▪▪ ]. Both studies revealed the benefit of ultrasound guidance in achieving higher quality airway anesthesia, shorter time to intubation, and increased patient comfort [11,12 ▪▪ ]. Though not described specifically in these studies, we posit that the use of ultrasound guidance for the superior laryngeal nerve block may be particularly beneficial in patients for whom landmark techniques may be more difficult, due to body habitus, aberrant anatomy, and/or distortion of normal airway landmarks.…”
Section: Regional Anesthesia Vs Topicalizationmentioning
confidence: 97%
“…Additionally, both nebulization and topicalization may take more time to perform to achieve adequate anesthesia, are dependent on delivery systems or devices, and may provide less dense coverage compared with targeted nerve blocks. This is supported by multiple studies revealing that nerve blocks led to higher quality of airway anesthesia (usually assessed by either the performer of the awake intubation or an independent observer), as well as a higher degree of patient comfort and postoperative patient satisfaction [11,12 ▪▪ ,13–23]. Whereas most studies compared the efficacy of the addition of nerve blocks to nebulization, an interesting study by Khandelwal et al [16] assessed the addition of nebulization to nerve blocks.…”
Section: Regional Anesthesia Vs Topicalizationmentioning
confidence: 99%
See 3 more Smart Citations